Political Connection, Tax Avoidance, and Firm Value During Kabinet Kerja Reign: The Case in Jakarta Islamic Index - Versiandika Yudha Pratama (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of political connection on firm value through tax avoidance as a mediating variable on companies listed in the Jakarta Islamic Index during Kabinet Kerja reign. This research includes quantitative research and the data used are secondary data from the company's annual report. With the purposive sampling method, obtained 103 companies that are used as research samples. Path analysis test was used to analyze data and hypothesis test. The results of the study show that the political connection and tax avoidance partially or simultaneously affect the value of companies listed in the Jakarta Islamic Index during Kabinet Kerja reign. Meanwhile, the political connection has no effect on tax avoidance, so it can be ascertained that tax avoidance does not mediate (unmediated) the effect of political connection on firm value in companies listed on the Jakarta Islamic Index during Kabinet Kerja reign.